2011
DOI: 10.1523/jneurosci.2717-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Reorganization of the Brain in Humans Following Spinal Cord Injury: Evidence for Underlying Changes in Cortical Anatomy

Abstract: Loss of somatosensory drive results in functional reorganization of the primary somatosensory cortex (SI). While the phenomenon of functional cortical reorganization is well established, it remains unknown whether in humans, functional reorganization results from changes in brain anatomy, or simply reflects an unmasking of already existing dormant synapses. In 20 subjects with complete thoracic spinal cord injuries (SCIs) and 23 controls, we used functional and structural magnetic resonance imaging to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
158
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(169 citation statements)
references
References 33 publications
(40 reference statements)
10
158
1
Order By: Relevance
“…29 Patients with complete SCI exhibit morphological changes such as reduced gray matter volume in the primary motor, medial prefrontal, cingulate, and cerebellar cortices, as well as diffusion tensor imaging changes in cortical and brainstem motor areas. 14,22,41 With the advent of functional imaging, various reorganization patterns were recognized. In a review by Kokotilo et al, 29 nearly half of the included studies documented a significant increase in activation magnitude in motor areas.…”
Section: Discussionmentioning
confidence: 99%
“…29 Patients with complete SCI exhibit morphological changes such as reduced gray matter volume in the primary motor, medial prefrontal, cingulate, and cerebellar cortices, as well as diffusion tensor imaging changes in cortical and brainstem motor areas. 14,22,41 With the advent of functional imaging, various reorganization patterns were recognized. In a review by Kokotilo et al, 29 nearly half of the included studies documented a significant increase in activation magnitude in motor areas.…”
Section: Discussionmentioning
confidence: 99%
“…Since this initial report, many investigators have reported functional reorganization of human S1 following various forms of deafferentation, such as limb amputation and complete spinal cord injury (Kaas, 1991;Flor et al, 1995Flor et al, , 1997Maihöfner et al, 2003;Wrigley et al, 2009;Henderson et al, 2011). Despite these findings, close inspection reveals that, in some individuals, deafferentation is not associated with significant cortical plasticity, whereas in others, a seemingly identical injury results in a significant change in cortical representations.…”
Section: Discussionmentioning
confidence: 99%
“…tDCS mechanisms are related to its influence on sodium and calcium channels opening and NMDA receptors excitability [50], while longlasting effects are analogous to activity-dependent synaptic plasticity, namely long-term potentiation (LTP) and long-term depression (LTD) [51][52][53]. Structural, functional and connectivity alterations at the cortical level have been described in patients with SCI, especially in the somatosensory cortex, consequently to the injury itself, as well as a result of the lack of sensory and motor inputs [54][55][56]; these changes being related to neuropathic pain [57]. Therefore, it is possible that patients with SCI sustain a decline in plasticity mechanisms as compared to those observed in healthy subjects, and therefore, tDCS related neuroplastic mechanisms may occur in a delayed manner.…”
Section: Delayed Tdcs Effects On Pain Reductionmentioning
confidence: 99%